2007
DOI: 10.1007/s00408-007-9027-9
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Muscle Strength in the Physically Active Elderly

Abstract: Advancing age is associated with a decline in the strength of the skeletal muscles, including those of respiration. Respiratory muscles can be strengthened with nonrespiratory activities. We therefore hypothesized that regular exercise in the elderly would attenuate this age-related decline in respiratory muscle strength. Twenty-four healthy subjects older than 65 years were recruited (11 males and 13 females). A comprehensive physical activity survey was administered, and subjects were categorized as active (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 23 publications
1
39
0
10
Order By: Relevance
“…DePalo found that abdominal exercise significantly increases transdiaphragmatic pressure that results in an increase in PImax and PEmax in healthy adults [10]. Summerhill found that active elderly subjects have higher PEmax and PImax compared to those in sedentary subjects [16]. Moreover, they speculated that physical activity involving the trunk and abdominal muscles might raise the intra-abdominal pressure; thus, enhancing respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…DePalo found that abdominal exercise significantly increases transdiaphragmatic pressure that results in an increase in PImax and PEmax in healthy adults [10]. Summerhill found that active elderly subjects have higher PEmax and PImax compared to those in sedentary subjects [16]. Moreover, they speculated that physical activity involving the trunk and abdominal muscles might raise the intra-abdominal pressure; thus, enhancing respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, changes in the skeletal muscles due to aging can compromise respiratory muscle function [10][11][12] . Therefore, the results obtained in this study suggest that elderly under pre-frailty condition may present lower hand grip strength associated with reduced respiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…The aging process promotes the decrease in muscle mass, strength and function, with repercussion in the respiratory muscles [10][11][12] . This situation may impact the performance of daily living activities, as well as in the functional capacity 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Estudo anterior indicou que o exercício aeróbio regular previne reduções na FMR relacionadas ao envelhecimento. 7 A dança é uma excelente forma de exercício físico aeróbico, e vários estudos [8][9][10] vêm demonstrando a sua importância para a manutenção da força muscular, sustentação, equilíbrio e potência aeróbia na população idosa.…”
Section: Introductionunclassified
“…Ao realizar manobras que aumentam a pressão intra-abdominal, o diafragma é ativado para minimizar a transmissão de alta pressão intra-abominal ao tórax. 27,28 Contraditoriamente aos resultados encontrados no presente estudo, onde houve variação significativa apenas da PEmax, Summerhill et al 7 encontraram melhora tanto da PImax quanto da PEmax de idosos. Segundo os mesmos autores, os idosos ativos rotineiramente envolvidos em atividades vigorosas que elevavam a pressão intra-abdominal tendem a fortalecer tanto o diafragma quanto a musculatura abdominal.…”
unclassified